2016
DOI: 10.1111/ceo.12752
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment for diabetic vitreoretinal diseases: a review

Abstract: Over the past four decades, advancements in surgical instrumentations and techniques have significantly improved the postoperative anatomical and visual outcomes of patients with various diabetic vitreoretinal diseases. In particular, surgical interventions for previously serious and untreatable blinding proliferative diabetic retinopathy can now be performed, with much better results. The advents of micro incisional vitrectomy system with better visualization system like binocular indirect ophthalmomicroscope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 81 publications
1
46
0
5
Order By: Relevance
“…Another important postoperative complication was elevated IOP in nine cases (20%), Sternfeld et al described similar findings in their retrospective studies of vitrectomised eyes [10].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Another important postoperative complication was elevated IOP in nine cases (20%), Sternfeld et al described similar findings in their retrospective studies of vitrectomised eyes [10].…”
Section: Discussionsupporting
confidence: 59%
“…In our study we did not document a case of hypotony. Sternfeld et al presented 16% of patients after PPV with hypotony [10].…”
Section: Discussionmentioning
confidence: 99%
“…Although the recently reported results from the DRCR.net Protocol T study showed substantially better visual outcomes, the DRCR.net protocols are difficult to follow in a real-life setting for clinicians in most parts of the world [21][22][23] . The pathogenesis of DME is complicated and, in addition to VEGF, also involves inflammatory cytokines and even vitreoretinal interface abnormalities [24][25][26] . Current mainstays of DME management are control of systemic factors, focal/grid laser for non-center-involving DME, anti-VEGF agents for center-involving DME, steroids, and vitrectomy [25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of DME is complicated and, in addition to VEGF, also involves inflammatory cytokines and even vitreoretinal interface abnormalities [24][25][26] . Current mainstays of DME management are control of systemic factors, focal/grid laser for non-center-involving DME, anti-VEGF agents for center-involving DME, steroids, and vitrectomy [25][26][27] . The ability to identify early on those patients who are likely to respond poorly to long-term anti-VEGF therapy would allow more timely consideration of alternative treatment regimens that might prove more effective in optimizing visual outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Results were not uniformly positive, however, as there was a relatively high incidence of severe complications (e.g., loss of light perception was 20% in the DRVS study of severe non-clearing VH). Technological innovations (e.g., introduction of intraoperative laser photocoagulation, improved fiberoptic illumination with the evolution of bimanual dissection, development of small-gauge instrumentation) substantially reduced the rate of complications and extended the indications for surgery in DR beyond the initial indications of severe non-clearing VH, traction retinal detachment (RD), and traction-rhegmatogenous RD, to epiretinal membrane (ERM), vitreomacular traction, diffuse macular edema, neovascular glaucoma (NVG), and anterior hyaloid fibrovascular proliferation [5] . Somewhat more controversial indications include non-tractional macular edema and combined vitrectomy with cataract surgery.…”
Section: Introductionmentioning
confidence: 99%